THE THEORETICAL SUBSTANTIATION OF APPLICAITION OF ECOLOGICAL METHODS OF PRESOWING SEEDS - T S Nizharadze (RUDN Journal of Ecology and Life Safety, 2015)
Theoretically substantiated the use of ecologically electrophysical methods of influence on the seeds of cereal crops to improve their sowing qualities of, supported by the results of many years of experience